Analysing humanities scholars’ data seeking behaviour patterns using Ellis' model - Wenqi Li; Pengyi Zhang; Jun Wang (Information Research: An International Electronic Journal)
Introduction. Much of humanities data are existing materials. Yet there are few works examining humanities scholars’ data seeking behaviours. The study aims to address this gap building upon Ellis’ model.